The Synergy Between Financial Education, Economic Well-Being, and Financial Stress: An Analysis of Interconnections and Reciprocal Effects - Moreira-Choez, Jenniffer (2023)
Background: Economic well-being and financial stress have been identified as crucial factors determining quality of life. This study aims to analyze financial education, economic well-being, financial stress, and their interrelations. With this, we seek to provide a more nuanced insight into the financial reality and its implications on individuals' quality of life, which has contributed to the enrichment of the field of study in question. Methods: The research is framed within an applied inquiry paradigm, with a quantitative approach. The survey technique was used, followed by subsequent statistical analysis. The sample consisted of 100 faculty members from the Technical University of Manabí. Results: Among the results, it was highlighted that financial education was positively associated with age, education, and marital status. This indicates that as people age, they acquire more financial knowledge and skills, resulting in better financial education. Conclusions: Among the most relevant conclusions, it supports the idea that financial education and economic well-being are interrelated and can be influenced by individual and socioeconomic factors. It is essential to address financial education and promote healthy financial practices from an early age, to provide opportunities for continuous learning throughout life.